Effect of Deformation-induced Residual Stress on Peel Strength of Polymer Laminated Sheet Metal. Issue 10 (2nd October 2016) - Noori, Hadi; Jain, Mukesh; Nielsen, Kent; Brandys, Frank
Abstract : The adhesion between adhesively bonded polymer film and a metallic sheet substrate in a polymer laminated sheet metal (PLSM) subjected to large deformation, such as in a forming process, is influenced by two deformation-induced factors. These are (i) evolution of surface roughness of metallic substrate with applied strain and (ii) development of residual stress in the polymer adherend (polymer film with a thin uniform adhesive layer on one side) arising from significant differences in the deformation behavior of metal and polymeric components. A new experimental methodology was devised in this study to decouple the effects of substrate surface roughness and residual stress on interfacial peel strength (IPS) of uniaxially deformed PLSMs. This methodology was based on 180° peel testing of PLSM specimens prepared under two different lamination conditions, one involving systematic pre-straining in uniaxial tension of the metallic substrate prior to laminations and the other involving post-lamination pre-straining of the PLSM. The role of pre-strain and peel test speed, for the above laminations conditions, were critically analyzed for their effect on IPS of two differently tailored PLSM systems. The IPS results were attributed to the effect of deformation-induced residual stress and metallic surface roughness. The analysis suggests that IPS is strongly dependent upon the residual stress induced by uniaxial deformation but only marginally on substrate surface roughness depending upon the constituents (film and adhesive) of the adherend. The magnitude of pre-strain was inversely and non-linearly related to IPS for both deformed PLSMs. Peel test speed, on the other hand, showed a more complex behavior in terms of IPS for the two PLSM systems.